Endocannabinoid System in Spinocerebellar Ataxia Type-3 and Other Autosomal-Dominant Cerebellar Ataxias: Potential Role in Pathogenesis and Expected Relevance as Neuroprotective Targets - Gómez-Ruiz, María; Rodríguez-Cueto, Carmen; Luna-Piñel, Eva; Hernández-Gálvez, Mariluz; Fernández-Ruiz, Javier (Frontiers in Molecular Neuroscience, 2019)
Spinocerebellar ataxias (SCAs) are a group of hereditary and progressive neurological disorders characterized by a loss of balance and motor coordination typically associated with cerebellar atrophy. The most prevalent SCA types are all polyQ disorders like Huntington’s disease, sharing the most relevant events in pathogenesis with this basal ganglia disorder, but with most of the damage concentrated in cerebellar neurons, and in their afferent and efferent connections (e.g., brainstem nuclei). SCAs have no cure and effective symptom-alleviating and disease-modifying therapies are not currently available. However, based on results obtained in studies conducted in murine models and information derived from analyses in post-mortem tissue samples from patients, which show notably higher levels of CB1 receptors found in different cerebellar neuronal subpopulations, the blockade of these receptors has been proposed for acutely modulating motor incoordination in cerebellar ataxias, whereas their chronic activation has been proposed for preserving specific neuronal losses. Additional studies in post-mortem tissues from SCA patients have also demonstrated elevated levels of CB2 receptors in Purkinje neurons as well as in glial elements in the granular layer and in the cerebellar white matter, with a similar profile found for endocannabinoid hydrolyzing enzymes, then suggesting that activating CB2 receptors and/or inhibiting these enzymes may also serve to develop cannabinoid-based neuroprotective therapies. The present review will address both aspects. On one hand, the endocannabinoid system becomes dysregulated in the cerebellum and also in other CNS structures (e.g., brainstem, basal ganglia) in SCAs, which may contribute to the progression of pathogenic events in these diseases. On the other hand, these endocannabinoid alterations may be pharmacologically corrected or enhanced, and this may have therapeutic consequences, either alleviating specific symptoms or eliciting neuroprotective effects, an objective presently under investigation.